A traceability model for rental equipment in support companies within the oil and gas industry - Asep Endih Nurhidayat; Rina Fitriana; Didien Suhardini; Asri Nugrahanti; Sannia Mareta (SINERGI, 2026)
Inefficiencies in equipment rental management within the oil and gas sector often lead to low transparency, slow data flow, and operational inaccuracies. This study aims to design and simulate a traceability model integrating Blockchain, the Internet of Things (IoT), and Quick Response (QR) Code technologies to improve data integrity and process efficiency. Using a mixed-method approach with object-oriented analysis and design under the Business Process Model and Notation (BPMN) framework, the system was developed and simulated through Bizagi Modeler. The proposed model consists of three components: the Tool Flow Sub-Model for equipment lifecycle tracking, the Document Flow Sub-Model for secure digital record management through blockchain, and the Grand Design Model that integrates processes and stakeholders into a unified traceability framework. Simulation results indicated a 91.7% improvement in process efficiency, reflecting significant reductions in transaction time and human error compared to the manual system. The integration of Blockchain, IoT, and QR Code technologies offers a novel approach to enhancing traceability and transparency in the oil and gas equipment rental industry. This field has been rarely addressed in previous studies. The findings demonstrate improved operational performance and stakeholder trust. However, further validation through real-world implementation and scalability testing is recommended for future research.